Marketing Communication Strategy of Youth Works Breakfast Week (Pasar Kamu) in Increasing Local Tourist Visits in Kampoeng Lama Tourist Village, Deli Serdang Regency - Muhammad Fadli; Rahmanita Ginting; Dewi Kurniawati (Jurnal Multidisiplin Madani, 2024)
This research aims to analyze the marketing communication strategy and analyze the obstacles of the marketing communication strategy of the Youth Works Breakfast Week (Pasar Kamu) in increasing local tourist visits in Kampoeng Lama Tourism Village, Deli Serdang Regency. This research uses constructivism paradigm with descriptive method and qualitative approach. The results of this study are that the marketing communication strategy of Pekan Sarapan Karya Muda (Pasar Kamu) in increasing local tourist visits at Kampoeng Lama Tourism Village, Deli Serdang Regency is by implementing marketing communication with the application of a marketing mix consisting of personal selling, advertising, as well as public relations, publicity and viral marketing. Through personal selling, managers and traders play an active and direct role in promoting to visitors who come Pasar Kamu. Advertising carried out by Pekan Sarapan Karya Anak Muda (Pasar Kamu) in collaboration with Metro Kampung as print media to promote activities that take place at Pekan Sarapan Karya Anak Muda (Pasar Kamu). Pasar Kamu's public relations role does not have a big impact because there is no public relations field. However, with the publicity carried out by Pasar Kamu to reach its target audience such as using goodie bags produced to do marketing with the public. There is viral marketing where visitors take the initiative to spread content containing information about Pasar Kamu on their Instagram and Tiktok social media accounts so that it becomes viral and succeeds in increasing tourist visits to Pasar Kamu